3D ophthalmic ultrasonography at the slit lamp using existing ultrasound systems. - Jack O Thomas; Josiah K To; Parsa Riazi Esfahani; Frithjof Kruggel; William C Tang; Andrew W Browne (PLoS ONE)
Purpose This study aims to explore the feasibility and performance of three-dimensional ultrasound (3DUS) imaging in ophthalmology using commercially available ultrasound probes adapted to a slit lamp. Significance Despite ultrasound's long-standing application in eye care for visualizing ocular components, the evolution of 3DUS technology has remained inactive, with limited development and commercial availability. This study introduces a novel method that could potentially enhance ophthalmic diagnostics and treatment planning by providing comprehensive 3D views of ocular structures using existing ultrasound probes adapted to the conventional slit lamp. Methods A custom system was designed for mounting a linear actuator to a slit lamp and enabling the horizontal actuation of any ultrasound probe. Ophthalmic and non-ophthalmic ultrasound probes were tested for their ability to reconstruct 3DUS images of the posterior pole. The study involved designing and evaluating three US phantoms ex vivo and performing in vivo imaging on human subjects to assess the system's applicability. Results The system successfully acquired 3D volume scans of phantoms and live human eyes, demonstrating the system's potential for detailed ocular imaging. The adaptability of the device allowed for compatibility with various ultrasound probes. In vivo imaging revealed the system's capability to produce high-resolution 3D reconstructions of ocular structures, including eyes with pathological conditions. Conclusions The introduction of a slit lamp-mounted 3DUS system represents a significant advancement in ophthalmic ultrasonography, offering a practical and accessible solution for comprehensive 3D ocular assessments. The device's modularity and compatibility with existing ultrasound probes make it a versatile tool for a wide range of ophthalmic applications. Further research and clinical trials are needed to optimize the system's performance and validate its clinical utility.